Interventions for healthy aging among mature Black lesbians: Recommendations gathered through community-based research. (2nd November 2017) - Seelman, Kristie L.; Adams, Mary Anne; Poteat, Tonia
ABSTRACT: Black lesbians have unique needs for gerontological services that reflect their experiences of intersectional oppression and resilience. Yet there is a major knowledge gap about interventions that promote healthy aging in this population, as voiced by Black lesbians themselves. To address this need, 100 Black lesbians, ranging in age from 41 to 91, participated in focus groups in Atlanta, Georgia, to discuss their experiences of aging, health needs, and recommendations for interventions. Through thematic analysis, we identified six themes related to suggested approaches for healthy aging interventions. We discuss implications of these findings for aging practice and future research.